Study of Corrosion Resistance of Hybrid Structure of DP980 Two-Phase Steel and Laser-Welded 6013-T4 Aluminum Alloy - Antonio Faria Neto; Erica Ximenes Dias; Francisco Henrique Cappi Freitas; Cristina Sayuri Fukugauchi; Erick Siqueira Guidi; Marcelo Sampaio Martins; Antonio Jorge Abdalla; Marcelo dos Santos Pereira (Journal of Manufacturing and Materials Processing)
The future of the automotive industry appears to hinge on the integration of dissimilar materials, such as aluminum alloys and carbon steel. However, this combination can lead to galvanic corrosion, compromising the structural integrity. In this study, laser-welded joints of 6013-T4 aluminum alloy and DP980 steel were evaluated for their morphology, microhardness, and corrosion resistance. Corrosion resistance was assessed using the electrochemical noise technique over time in 0.1 M Na2SO4 and 3.5% NaCl solutions. The wavelet function was applied to remove the DC trend, and energy diagrams were generated to identify the type of corrosive process occurring on the electrodes. Corrosion on the electrodes was also monitored using photomicrographic images. Analysis revealed an aluminum–steel mixture in the melting zone, along with the presence of AlFe, AlFe3, and AlI3Fe4 intermetallic compounds. The highest Vickers microhardness was observed in the heat-affected zone, adjacent to the melt zone, where a martensitic microstructure was identified. The 6013-T4 aluminum alloy demonstrated the highest corrosion resistance in both media. Conversely, the electrochemical noise resistance was similar for the DP980 steel and the weld bead, indicating that the laser welding process does not significantly impact this property. The energy diagrams showed that localized pitting corrosion was the predominant form of corrosion. However, generalized and mixed corrosion were also observed, which corroborated the macroscopic analysis of the electrodes.